Practices on Technology Integration in ELT: A Review on Existing Researches - Gina Selvira Yanti; Rafika Nurhidayah (Universitas Nahdlatul Ulama Blitar, 2020)
The education 4.0 phenomenon is getting stronger day by day which makes the technology integration in ELT stands in a spotlight. For this reason, this paper aims to show and to describe some techniques or teaching procedures taken from the documented research articles; and to offer some suggestions for educators in Indonesia to integrate technology in their classrooms. This paper is done as a response to the increase need to integrate technology in teaching learning process, specifically, in English language teaching. This is a qualitative research in nature through searching, taking, reading, analyzing and concluding the results from the documented researches regarding to the topic. An empirical-based research was a focus for this research; thus, there are 11 researches in total within the year 2016-2020. This paper is hoped to be able to present, to describe, and to inspire scholars, researchers, teachers, and even decision-makers to apply more teaching learning process which tends to the education 4.0 atmospheres.